2012
DOI: 10.1016/j.socscimed.2012.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Contextualization of HIV and HPV risk and prevention among Pacific Islander young adults in Southern California

Abstract: HIV and sexually transmitted human papillomavirus (HPV) are associated with each other and with the development of comorbid cancer. Current epidemiology indicates that among Pacific Islanders in the United States, young adults are at highest risk of HIV and HPV. In our inductive community based participatory research study, we used focus groups and key informant interviews (March – August 2010) with young adults, parents, community leaders, and providers (n = 95) to identify and contextualize factors that shap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(38 citation statements)
references
References 39 publications
0
38
0
Order By: Relevance
“…18 Reluctance to engage with health care providers has been described in relation to other health problems that are viewed as stigmatising and risking family reputation in Pacific communities. 19 A diagnosis of diabetes could be a threat to self-pride and to their standing in the community for the men in our study. Men with diabetes have emphasised the importance of being active and economically independent to their overall health.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…18 Reluctance to engage with health care providers has been described in relation to other health problems that are viewed as stigmatising and risking family reputation in Pacific communities. 19 A diagnosis of diabetes could be a threat to self-pride and to their standing in the community for the men in our study. Men with diabetes have emphasised the importance of being active and economically independent to their overall health.…”
Section: Discussionmentioning
confidence: 75%
“…Shame and a feeling of failure can be a barrier to help‐seeking for those with diabetes, resulting in denial of the condition as well as reluctance to disclose their diagnosis to family members, especially amongst men . Reluctance to engage with health care providers has been described in relation to other health problems that are viewed as stigmatising and risking family reputation in Pacific communities …”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the methodologies of the selected papers indicated that most of the researchers (ten out of fourteen) adopted a qualitative approach (Dela Cruz et al, 2016;Devries et al, 2010;DiStefano et al, 2012;2013;Henderson et al, 2018;Hodge, 2014;Itty et al, 2014;Nonzee et al, 2018;Soon et al, 2015); three were based on quantitative analysis (Dwojak et al, 2015;Gabster et al, 2019;Tom et al, 2016); and one had a mixed-methods approach (Hodge et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…These teams typically relied on regular contact (i.e., meetings, conferences, and focus groups) to discuss and resolve challenges in research design and at other stages of the projects. The formation of advisory groups, comprised of both academic and community participants, was common in research with Indigenous Peoples (e.g., McWhirter, Mununggirritj, Marika, Dickinson, & Condon, ; Novins et al, ; Palacios & Kennedy, ; Richards & Mousseau, ; Smith, Christopher, & McCormick, ), HIV/AIDS‐focused studies (e.g., Abelsohn et al, ; Andrasik et al, ; Baptiste et al, ; Burkhalter et al, ; DiStefano et al, ; Nyamathi et al, ; Vallely et al, ), and research with older adults (e.g., Guo & Phillips, ; Klemm, Rempusheski, & Teixeira, ; Ottmann, Laragy, Allen, & Feldman, ; Perry & Ziemba, ; Scharlach & Sanchez, ; West & Graham, ; Wethington et al, ). These efforts were sometimes described as attempts to address inherent power imbalances between university researchers and participants (e.g., Tobias, Richmond & Luginaah, ).…”
Section: Resultsmentioning
confidence: 99%
“…McWhirter, Mununggirritj, Marika, Dickinson, & Condon, 2012;Novins et al, 2012;Palacios & Kennedy, 2010;Richards & Mousseau, 2012;Smith, Christopher, & McCormick, 2004), HIV/AIDS-focused studies (e.g., Abelsohn et al, 2015;Andrasik et al, 2012;Baptiste et al, 2006;Burkhalter et al, 2013;DiStefano et al, 2012;Nyamathi et al, 2004;Vallely et al, 2009), and research with older adults (e.g., Guo & Phillips, 2006;Klemm, Rempusheski, & Teixeira, 2013;Ottmann, Laragy, Allen, & Feldman, 2011;Perry & Ziemba, 2014;Scharlach & Sanchez, 2011;West & Graham, 1999;Wethington et al, 2007). These efforts were sometimes described as attempts to address inherent power imbalances between university researchers and participants (e.g., Tobias, Richmond & Luginaah, 2013).…”
Section: Pr Designmentioning
confidence: 99%